2002
DOI: 10.1046/j.1440-1843.2002.00396.x
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory morbidity and lung function in two Aboriginal communities in Western Australia

Abstract: Our findings show a low prevalence of asthma in children, a high prevalence of respiratory symptoms and low levels of lung function in remote Aboriginal communities. The greater prevalence of respiratory morbidity in the desert community was not explained by diagnosed asthma, airway hyperresponsiveness or cigarette smoking. The role of infection requires further investigation. The results suggest that the lower lung function observed in Aboriginal communities (compared with non-Aboriginal communities) results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 27 publications
1
19
0
Order By: Relevance
“…However, there was a large variation in the differences observed. For example, Chandler and colleagues 20 noted Indigenous FEV 1 and FVC values to be ≤ 15% lower, whereas the studies by Verheijden and colleagues 15 and Veale and colleagues 17 reported results to be as much as 30% lower. Musk and colleagues 13 and Bucens and colleagues 14 noted that their spirometry results were similar to previous studies and lower than those in people of European ancestry, but did not specify how much lower.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, there was a large variation in the differences observed. For example, Chandler and colleagues 20 noted Indigenous FEV 1 and FVC values to be ≤ 15% lower, whereas the studies by Verheijden and colleagues 15 and Veale and colleagues 17 reported results to be as much as 30% lower. Musk and colleagues 13 and Bucens and colleagues 14 noted that their spirometry results were similar to previous studies and lower than those in people of European ancestry, but did not specify how much lower.…”
Section: Resultsmentioning
confidence: 99%
“…All included studies involved prospective cohort groups and all followed appropriate ATS–ERS criteria when performing spirometry. The aims of the studies differed and included observing lung function, 20 examining influencing factors 13 15 and developing reference equations for spirometry in Indigenous Australians ( n = 5) 16 . ‐ 19 , 21 None of the included studies followed all the ATS–ERS and GLI criteria needed to develop reference equations or validate the spirometry results (Box 4).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The GLI-2012 African-American equations are 14-16% lower than Caucasian values. Therefore, if previously conducted studies [21][22][23][24] on Indigenous Australian reference values were accurate (FEV 1 and FVC values up to 25% lower than Caucasians), then the African-American equation may be more appropriate. However, we found spirometry values for all Australian Indigenous ethnicities to be higher than the African-American values, with 15-18% of participants having z-scores above the ULN (>1.64).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies [21][22][23][24][25] have reported Australian Aboriginals to have forced expiratory volume in 1 s (FEV 1 ) and forced vital capacity (FVC) values up to 25% and 30% lower, respectively, than healthy Caucasians. However, our systematic review 26 found that in these studies, spirometry was not performed according to the current American Thoracic Society (ATS), European Respiratory Society (ERS) or GLI guidelines.…”
Section: Introductionmentioning
confidence: 99%